Industry integration and stock price synchronicity - CHENG, Hao (Institutional Knowledge at Singapore Management University, 2017)
This paper provides an alternative explanation of the negative relationship between price synchronicity and proprietary right protection that are uncorrelated to the information hypothesis. Using empirical data for 40 countries, we show that stock market volatility and firm size have significant impact on stock price synchronicity. We find significant correlations of international R2 disparity with industry structure integrations. The derived industry integration indices that capture industry correlations significantly explain cross-sectional and temporal variations in price synchronicity. The results imply that tighter industry integration leads to higher R2, and also explain away the property rights factor found in the information hypothesis.